Inequalities in Alcohol-Related Mortality in 17 European Countries: A Retrospective Analysis of Mortality Registers - Mackenbach, Johan P; Kulhánová, Ivana; Bopp, Matthias; Borrell, Carme; Deboosere, Patrick; Kovács, Katalin; Looman, Caspar W N; Leinsalu, Mall; Mäkelä, Pia; Martikainen, Pekka; Menvielle, Gwenn; Rodríguez-Sanz, Maica; et al. (PLoS medicine, 2015)
BACKGROUND: Socioeconomic inequalities in alcohol-related mortality have been documented in several European countries, but it is unknown whether the magnitude of these inequalities differs between countries and whether these inequalities increase or decrease over time. METHODS AND FINDINGS: We collected and harmonized data on mortality from four alcohol-related causes (alcoholic psychosis, dependence, and abuse; alcoholic cardiomyopathy; alcoholic liver cirrhosis; and accidental poisoning by alcohol) by age, sex, education level, and occupational class in 20 European populations from 17 different countries, both for a recent period and for previous points in time, using data from mortality registers. Mortality was age-standardized using the European Standard Population, and measures for both relative and absolute inequality between low and high socioeconomic groups (as measured by educational level and occupational class) were calculated. Rates of alcohol-related mortality are higher in lower educational and occupational groups in all countries. Both relative and absolute inequalities are largest in Eastern Europe, and Finland and Denmark also have very large absolute inequalities in alcohol-related mortality. For example, for educational inequality among Finnish men, the relative index of inequality is 3.6 (95% CI 3.3-4.0) and the slope index of inequality is 112.5 (95% CI 106.2-118.8) deaths per 100,000 person-years. Over time, the relative inequality in alcohol-related mortality has increased in many countries, but the main change is a strong rise of absolute inequality in several countries in Eastern Europe (Hungary, Lithuania, Estonia) and Northern Europe (Finland, Denmark) because of a rapid rise in alcohol-related mortality in lower socioeconomic groups. In some of these countries, alcohol-related causes now account for 10% or more of the socioeconomic inequality in total mortality. Because our study relies on routinely collected underlying causes of death, it is likely that our results underestimate the true extent of the problem. CONCLUSIONS: Alcohol-related conditions play an important role in generating inequalities in total mortality in many European countries. Countering increases in alcohol-related mortality in lower socioeconomic groups is essential for reducing inequalities in mortality. Studies of why such increases have not occurred in countries like France, Switzerland, Spain, and Italy can help in developing evidence-based policies in other European countries.
Keywords: senioři; disparity zdravotního stavu; mortalita; Prevalence; ethanol; zaměstnání; Retrospective Studies; Europe; Socioeconomic Factors; Health Status Disparities; Evropa; Middle Aged; Ethanol; registrace; mužské pohlaví; prevalence; Adult; Registries; socioekonomické faktory; ženské pohlaví; retrospektivní studie; Humans; Mortality; lidé středního věku; dospělí; Occupations; Female; Aged; lidé; Male